(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Liver cancer, particularly hepatocellular carcinoma (HCC), occurs from liver cell abnormalities, influenced by factors such viral hepatitis, obesity toxins and drugs. Non-Alcoholic Fatty Liver Disease (NAFLD) exacerbates liver disorders globally, marked by fat accumulation, whereas liver fibrosis raises cancer risk in NAFLD and Alcohol-Induced Liver Disease (ALD). Herbal medicine gains attraction for liver health, offering hepatoprotective benefits. Medicinal plant metabolites, particularly polyphenols, display antioxidative effects, possibly suppressing cancer cell development. This work focuses on evaluating the possible antioxidant and cytotoxic effects of Chrozophora rottleri fruit ethanol extract (CRFEE) using in-vitro experiments. The antioxidant capacity of CRFEE was examined by hydroxyl radical and nitric oxide scavenging experiments. CRFEE revealed considerable scavenging efficacy against both radicals, suppressing hydroxyl radicals by 48.25% with an IC50 of 35.08±1.62 μg/ml and nitric oxide by 49.35% with an IC50 of 307.44±2.28 μg/ml. Notably, CRFEE displayed better antioxidant efficiency compared to the standard antioxidant, butylated hydroxyl toluene (BHT), in neutralizing hydroxyl radicals. Additionally, the in-vitro cytotoxicity of Chrozophora rottleri fruit ethanol extract (CRFEE) was examined using the MTT test on HepG-2 cell line cultures. CRFEE had strong detrimental effects on HepG-2 cells, with higher dosages resulting to a major loss in cell viability. The IC50 value for CRFEE was determined 63±0.08μg/mL, suggesting its efficacy in reducing HepG-2 cell proliferation. The results demonstrate substantial antioxidant activity and cytotoxic effects against liver cancer cells (HepG-2 cell line). The bioactive chemicals contained in CRFEE show potential for future pharmaceutical applications, underscoring the relevance of natural-based research in cancer therapy and the necessity for further exploration in vivo.